Hepatic myofibroblasts exert immunosuppressive effects independent of the immune checkpoint regulator PD-L1 in liver metastasis of pancreatic ductal adenocarcinoma - Beckinger, Silje; Daunke, Tina; Aldag, Leon; Krüger, Sandra; Heckl, Steffen; Wesch, Daniela; Schäfer, Heiner; Röcken, Christoph; Rahn, Sascha; Sebens, Susanne (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) represents the 4th most common cause of cancer-related deaths in Western countries. Most patients are diagnosed at advanced stages, often already with metastases. The main site of metastasis is the liver and hepatic myofibroblasts (HMF) play a pivotal role in metastatic outgrowth. Immune checkpoint inhibitors (ICI) targeting programmed death ligand 1 (PD-L1) or programmed cell death protein 1 (PD-1) improved treatment of several cancers but not of PDAC. Therefore, this study aimed to better understand the impact of HMF on PD-L1 expression and immune evasion of PDAC cells during liver metastasis. Immunohistochemical analysis of liver tissue sections of PDAC patients revealed that HMF represent an abundant stroma population in liver metastases, with clear differences in the spatial distribution in small ( 1500 µm) and large (> 1500 µm) metastases. In the latter, PD-L1 expression was mainly located at the invasion front or evenly distributed, while small metastases either lacked PD-L1 expression or showed mostly weak expression in the center. Double stainings revealed that PD-L1 is predominantly expressed by stromal cells, especially HMF. Small liver metastases with no or low PD-L1 expression comprised more CD8+ T cells in the tumor center, while large metastases exhibiting stronger PD-L1 expression comprised less CD8+ T cells being mostly located at the invasion front. HMF enriched spheroid cocultures with different ratios of PDAC cells and HMF were established well mimicking conditions of hepatic metastases in situ. Here, HMF impaired the release of effector molecules by CD8+ T cells and the induction of PDAC cell death, an effect that was dependent on the amount of HMF but also of PDAC cells. ICI treatment led to elevated secretion of distinct CD8+ T cell effector molecules but did not increase PDAC cell death under either spheroid condition. Our findings indicate a spatial reorganization of HMF, CD8+ T cells, and PD-L1 expression during progression of PDAC liver metastases. Furthermore, HMF potently impair the effector phenotype of CD8+ T cells but the PD-L1/PD-1 axis apparently plays a minor role in this scenario suggesting that immune evasion of PDAC liver metastases relies on other immunosuppressive mechanisms.